1987
DOI: 10.1093/oxfordjournals.eurheartj.a062272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of persiting myocardial sinusoids on left ventricular performance in pulmonary atresia with intact ventricular septum

Abstract: The effects of persisting right ventricular myocardial sinusoids on left ventricular global and regional function were studied in 13 patients with pulmonary atresia and intact ventricular septum. Persisting myocardial sinusoids allow the inflow of undersaturated blood into the coronary circulation with subsequent myocardial ischaemia. 7 patients had myocardial sinusoids (group 1). 6 patients had normal coronary perfusion (group 2) The measures of global left ventricular function (ejection fraction, left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The influence of associated coronary abnormalities on LV function has been reported. 28,29 Even in the absence of abnormal coronary sinusoidal communications, medial thickening of intramyocardial coronary arteries, discrete areas of fibrosis and calcification, and high levels of endomysial collagen suggestive of chronic ischemia have been documented. 30,31 Our finding of scatteredareas of LGE in the left ventricle is perhaps a reflection of these discrete pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of associated coronary abnormalities on LV function has been reported. 28,29 Even in the absence of abnormal coronary sinusoidal communications, medial thickening of intramyocardial coronary arteries, discrete areas of fibrosis and calcification, and high levels of endomysial collagen suggestive of chronic ischemia have been documented. 30,31 Our finding of scatteredareas of LGE in the left ventricle is perhaps a reflection of these discrete pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that patients with RV-to-coronary connections and coronary abnormalities have a higher incidence of wall motion abnormalities (which might reflect ongoing ischemia), and that such patients are at risk of late death [5]. Hausdorf and associates [6] found a high degree of coincidence between regional wall motion abnormalities and myocardial perfusion topography resulting from persisting myocardial sinusoids. Fenton and associates [20] attributed the most common cause of interim mortality to abnormal myocardial perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, these patients have a small, hypertrophied right ventricle (RV) with supra-systemic pressure and sinusoidal communication between the RV and the coronary artery [1,2]. Many authors have noticed the possible deleterious effects associated with this situation, i.e., the progression of RV-to-coronary connections and subsequent coronary artery stenosis [3][4][5][6], potential RV 'steal' and coronary ischemia after RV decompression [4,7], impaired left ventricular compliance [8], left ventricular hypertrophy with a prominent subaortic septal bulge [9,10], fibroelastosis of the left ventricle (LV) [10], and an impaired LV function after a Fontan procedure [11] or even after biventricular repair [12]. A surgical trial to prevent these deleterious effects was first described by Waldman and associates [13].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have previously assessed the influence of PAIVS-associated coronary abnormalities on LV function [23,24]. Hausdorf et al demonstrated apical hypokinesia in patients with communications between myocardial sinusoid and left anterior descending coronary artery before RV decompression [23].…”
Section: Discussionmentioning
confidence: 99%
“…Hausdorf et al demonstrated apical hypokinesia in patients with communications between myocardial sinusoid and left anterior descending coronary artery before RV decompression [23]. After surgical RV decompression, Gentles et al have similarly found regional LV dysfunction in patients with coronary abnormalities studied at a median of 20 months after operation [24].…”
Section: Discussionmentioning
confidence: 99%